Daily variation in time-trial sporting performance: A systematic review - Bommasamudram, T.; Ravindrakumar, A.; Varamenti, E.; Tod, D.; Edwards, B. J.; Peter, I. G.; Pullinger, S. A. (Chronobiology International, 2022)
Few functional measures related to time-trial display diurnal variation. The diversity of tests/protocols used to assess time-trial performance on diurnal effects and the lack of a standardised approach hinder agreement in the literature. Therefore, the aims of the present study were to investigate and systematically review the evidence relating to time-of-day differences in time-trial measures and to examine the main aspects related to research design important for studies of a chronobiological nature. The entire content of Manipal Academy of Higher Education electronic library and Qatar National Library, and electronic databases: PubMed (MEDLINE), Scopus and Web of Science were searched. Research studies published in peer-reviewed journals and non-peer reviewed studies, conducted in male adult participants aged =18 y before November 2021 were screened/included. Studies assessing tests related to time-trials in any modality between a minimum of 2 time-points during the day (morning [06:30-10:30 h] vs evening [14:30-20:00 h]) were deemed eligible. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) process was used to assess the evidence to inform recommendations. The primary search revealed that a total of 10 from 40 articles were considered eligible and subsequently included. Six were conducted using cycling, two using running and two using swimming as the mode of exercise. Distances ranged from 1 to 16.1-km in distance or 15 to 20-min time in the cycling and running time-trials, and 50 to 200-m in the swimming time-trials. Only four studies found one or several of their performance variables to display daily variations, with significantly better values in the evening; while six studies found no time-of-day significance in any variables assessed. The magnitude of difference ranged from 2.9% to 7.1% for performance time to complete a cycling time-trial, while running and swimming did not find any differences for performance time. Power output during a 16.1-km time trial in cycling also found evening performance to be significantly better by 10%. The only other observed differences were stroke rate and stroke length during a swimming time-trial and stroke rate (cycles.min-1) during a cycling time-trial. The magnitude of difference is dependent on exercise modality, individual chronotype, the training status of the individual and sample size differences. The lack of diurnal variation present in the majority of studies can in-part be explained with some of the methodological limitations and issues present related to quality and control. It is paramount that research assessing diurnal variation in performance uses appropriate session timings around the core body temperature minimum (~05:00 h; morning) and maximum (~17:00 h; evening). Although, differences in motivation/arousal, habitual training times, chronotypes and genotypes could provide an explanation as to why some studies/variables did not display time-of-day variation, more work is needed to provide an accurate conclusion. There is a clear demand for a rigorous, standardised approach to be adopted by future investigations which control factors that specifically relate to investigations of time-of-day, such as appropriate familiarisation, counterbalancing the order of administration of tests, providing sufficient recovery time between sessions and testing within a controlled environment.